Sexual Education for Parents and Teachers of Teenagers with Special Needs - Penny Handayani; Weny Savitry S. Pandia; Agustin Angelia Putri; Lidia Wati; Vincentia Visi P; Agatha Rizky (MITRA: Jurnal Pemberdayaan Masyarakat, 2019)
Yayasan Wahana Inclusive Indonesia (YWII) is an institution engaged in providing services for children with special needs, people with disability, and inclusive society. YWII provides services that include counseling, development of individual learning programs (PPIs), support services for children with special needs, and training for educators, schools, parents, and communities. Educational and training activities are conducted by helping children with special needs to learn a few things they need most in their daily lives. Based on the children’s needs, the Master’s Program of Child and Adolescent Psychology Professionals, Faculty of Psychology, Atma Jaya Catholic University, designed training-based interventions to improve the knowledge of students, teachers, and parents about sexual behaviors. Prior to the intervention, the researcher conducted an assessment to determine the causes of "inapproriate" sexual behavior problems that occurred in the YWII environment. The data was collected through instruments such as interview, observation, and FGD. The collected data was then analyzed using the concepts of problem tree and destination tree. Based on the assessment results, it can be concluded that one of the challenges faced by YWII is related to the provision of sexual education to students or children. Adolescents with special needs have not yet had an awareness of their development from children to adolescents that is followed by sexual change or development and how they should respond to the changes. As a result, they are often considered to exhibit behaviors considered rude and vulnerable to sexual harassment. Training-based interventions were provided to parents and teachers at YWII to give them guidance and assistance to handle children with special needs on sexual education